Exploring adult-onset actinic prurigo in Thailand - Sangmala, Siripan; Wongpraparat, Chanisada; Silpa-archa, Narumol; Chaiyabutr, Chayada (Dermatology Reports, 2023)
Actinic prurigo (AP) is an uncommon photodermatosis. In European and Native American populations, AP is more common in young women and demonstrates clinical improvement or remission in adulthood. The clinical signs of AP differ in Asians because the disorder typically occurs in adults (adult-onset AP) and is clinically persistent. The objective of this study was to investigate the characteristics and outcomes of patients with AP in Thailand. A total of 15 cases with AP were evaluated. All of them were adultonset AP (mean onset age of 45.5 years). Males predominated (66.7%). The majority of them manifested with papules on the face and upper extremities. Mucositis was present in 2 patients. Phototesting revealed that the minimal erythematous dose (MED) for UVA decreased in 3 subjects and the MED for both UVA and UVB decreased in other 3 patients. A photo-provocation test was performed on 9 patients with normal MED, and 5 of them showed positive UVA photo-provocation, while 4 showed positive UVA and UVB photop-rovocation. A systemic immunosuppressant was prescribed in 60% of patients. Median time for clinical improvement was 8.6 months. Complete clinical remission was found in only 3 patients. Adult-onset AP has different clinical features and responds differently to treatment, compared to classical AP.